Inter-hospital transfer of ECMO-assisted patients with a portable miniaturized ECMO device: 4 years of experience. (January 2015) - Raspé, C; Rückert, F; Metz, D; Hofmann, B; Neitzel, T; Stiller, M; Gielen, S; Nestler, F; Ebbighausen, N; Steinke, T; Bucher, M; Bushnaq, H
Objectives: Extracorporeal membrane oxygenation (ECMO) in patients with severe pulmonary failure is able to keep patients alive until organ regeneration, until shunting out for further diagnostic and therapeutic options or until transportation to specialized centers. Nonetheless, extracorporeal techniques require a high degree of expertise, so that a confinement to specialized centers is meaningful. Following from this requirement, the need for inter-hospital transfer of patients with severely compromised pulmonary function is rising. Methods: We report about our experience with a portable ECMO system during inter-hospital air or ground transfer of patients with cardiopulmonary failure. Results: The portable ECMO system was used for transportation to the center and in-hospital treatment in 36 patients with an average age of 53 years suffering from respiratory failure. Accordingly, the ECMO system was implanted as a veno-venous extracorporeal system. Pre-ECMO ventilation time was 5.2 (2-9) days. Twelve patients were transported to our institution by ground and 24 patients by air ambulance over a median distance of 46 km. With the assistance of the ECMO device, prompt stabilization of cardiopulmonary function could be achieved in all patients without any technical complications. Post-ECMO ventilation was 9.8 days. Weaning from the ECMO system was successful in 61% of all patients after a median device working period of 12.7 days; median ICU stay was 34 days and a survival rate of 64% of patients was achieved. Technical (8%) and device-associated bleeding (11%)/thromboembolic (8%) complication rates showed very acceptable levels. Conclusion: Our experience demonstrates that miniaturized, portable ECMO therapy allows location-independent, out-of-center stabilization of pulmonary compromised patients with consecutive inter-hospital transfer and further in-house treatment, so that sophisticated ECMO therapy can be offered to every patient, even in hospitals with primary healthcare.